Impact of high-power and very high-power short-duration radiofrequency ablation on procedure characteristics and first-pass isolation during pulmonary vein isolation. (3rd October 2022) - Sallo, Z; Perge, P; Orban, G; Piros, K; Herczeg, S Z; Nagy, K V; Abraham, P; Osztheimer, I; Merkely, B; Geller, L; Szegedi, N
Abstract: Introduction: High-power short-duration (HPSD) radiofrequency ablation has been proposed as a method for producing rapid and effective lesions for pulmonary vein isolation (PVI). We aimed to evaluate the procedural characteristics and the first-pass isolation (FPI) rate of HPSD and very high-power short-duration (vHPSD) ablation compared to low-power long-duration (LPLD) ablation technique. Methods: 156 patients with atrial fibrillation (AF) were enrolled and assigned to LPLD, HPSD, or vHPSD PVI. The energy setting was 30W, 50W, and 90W in the LPLD, HPSD, and vHPSD groups, respectively. Results: Bilateral PVI was achieved in all cases. The procedure time was 85 [75–101] min, 79 [65–91] min, and 70 [53–83] min in the LPLD, HPSD, and vHPSD groups, respectively (p<0.0001). Left atrial (LA) dwelling times were also decreased significantly with the increase of RF energy (61 [55–70] min, 53 [41–56] min, and 45 [34–52] min, in the LPLD, HPSD, and vHPSD groups, respectively, p<0.0001). The total RF ablation time was 1567 [1366–1761] sec, 1398 [1021–1711] sec, and 336 [247–386] sec in the LPLD, HPSD, and vHPSD group, respectively (p<0.0001). The bilateral FPI rate was 57%, 78%, and 80% in the LPLD, HPSD, and vHPSD groups, respectively (p=0.0097). On the left side, FPI was achieved in 66% in the LPLD, 92% in the HPSD, and 85% in the vHPSD ablation group (p=0.0015). FPI on the right side was achieved in 72% in the LPLD, 88% in the HPSD, and 88% in the vHPSD ablation group (p=0.0188). The univariate analysis revealed that the use of HPSD (both sides: OR=2.72, 95% CI 1.15–6.44, p=0.023; right side: OR=2.90, 95% CI 1.02–8.20, p=0.045; left side: OR=5.91, 95% CI 1.84–19.04, p=0.003) and vHPSD (both sides: OR=2.90, 95% CI 1.24–6.44, p=0.014; right side: OR=3.09, 95% CI 1.09–8.74, p=0.045; left side: OR=2.89, 95% CI 1.13–7.43, p=0.027) ablation techniques were associated with a higher probability of FPI. The mid-term arrhythmia-free survival was similarly high in all three groups. Conclusion: Our prospective, observational cohort study showed that both HPSD and vHPSD RF ablation is effective, as it shortens procedure time and RF time and results in a higher rate of FPI compared to LPLD ablation. Moreover, the mid-term arrhythmia-free survival was similarly high in all three groups. In our study, no safety concerns were raised for HPSD or vHPSD ablation. Funding Acknowledgement: Type of funding sources: None.